Current Progress in Cancer Treatment Using Nanomaterials - Zhu, Ruirui; Zhang, Fangyuan; Peng, Yudong; Xie, Tian; Wang, Yi; Lan, Yin (Frontiers in Oncology, 2022)
The pathological processes of cancer are complex. Current methods used for chemotherapy have various limitations, such as cytotoxicity, multi-drug resistance, stem-like cells growth, and lack of specificity. Several types of nanomaterials are used for cancer treatment. Nanomaterials 1–100 nm in size have special optical, magnetic, and electrical characteristics. Nanomaterials have been fabricated for cancer treatments to overcome cytotoxicity and low specificity, and improve drug capacity and bioavailability. Despite the increasing number of related studies, few nanodrugs have been approved for clinical use. To improve translation of these materials, studies of targeted drug delivery using nanocarriers are needed. Cytotoxicity, enhanced permeability and retention effects, and the protective role of the protein corona remain to be addressed. This mini-review summarizes new nanomaterials manufactured in studies and in clinical use, analyses current barriers preventing their translation to clinical use, and describes the effective application of nanomaterials in cancer treatment.